Hubungan Time Management dengan Work-Life Balance pada Guru Wanita di Kecamatan Kuranji - Prasetia, Yoggi; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2025)
This study aims to examine the relationship between time management and work-life balance among female teachers in Kuranji District. The subjects consisted of 97 married female junior high school teachers who have children. A quantitative approach was used, employing Pearson’s product-moment correlation analysis. The research instruments included a time management scale and a work-life balance scale, both of which had been tested for validity and reliability, with Cronbach’s Alpha values of 0.897 and 0.899, respectively. The analysis results indicate a positive and significant relationship between time management and work-life balance, with a correlation coefficient of r = 0.205 and p = 0.044 (p < 0.05), although the strength of the relationship falls within the weak category. These findings suggest that the better female teachers are at managing their time, the higher their levels of balance between professional and personal life. The implications of this study underscore the importance of training and institutional support in enhancing time management skills to help female teachers achieve a more optimal work-life balance.